The role of adaptive resilience in the relationship between transformational leadership, affective commitment and turnover intention in the post COVID-19 era: a case of Vietnam - Ha, Minh Thi Phuong; Ho, Dung Tien; Nguyen, Long Ngoc (Business: Theory and Practice, 2024)
This study investigates the direct or indirect impact of transformational leadership and adaptive resilience on affective commitment and turnover intention. Qualitative research was conducted to validate the concepts and the research model and quantitative research was carried out to analyze data from 310 employees selected via convenient sampling in Vietnam. The results reveal that transformational leadership does not only directly affect adaptive resilience and turnover intention, but also indirectly and fully affects affective commitment via adaptive resilience, and indirectly and partially affects turnover intention via affective commitment and adaptive resilience. Furthermore, adaptive resilience significantly impacts turnover intention via affective commitment. There is no proof in the research that adaptive resilience directly affects turnover intention. This research has documented valuable experiences related to the adaptive resilience of organizations following social crises in the relationship between leadership and turnover for scholars and managers in the future.